The phenomenon of social isolation: The role of social media in the self-isolation tendencies of adolescents in Bengkulu Province - Muhammad Oktarianto; Rasianna BR Saragih; Neneng Cucu Marlina (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
The use of social media has been associated with an increased propensity for social isolation among adolescents. This study sought to examine the relationship between social media usage and social isolation among adolescents in Bengkulu Province by investigating the phenomenon of adolescent social isolation and the factors prompting individuals to withdraw from their social environments, utilising Marshall McLuhan's Media Ecology Theory as the theoretical framework. Employing a qualitative methodology with a phenomenological approach, this study delves into the subjective experiences of adolescents who engage in social isolation. Primary data were collected through interviews, observations, and documentation, whereas secondary data were sourced from literature reviews. Data analysis employed descriptive-analytical techniques, including data reduction, presentation, and verification. The findings indicate that external factors, such as negative behaviours in the social environment—(1) betrayal by trusted individuals, (2) experiences of sexual harassment, and (3) exposure to negative comments—are primary contributors to social isolation. Internal factors, including individual perceptions, psychological conditions, and social media, serve as supportive factors. Adolescents engaging in social isolation are particularly susceptible to mental health issues such as loneliness, stress, and depression. However, social media, in certain contexts, can function as a recreational tool and source of psychological support, helping adolescents cope with feelings of loneliness. Therefore, it can be concluded that social media can act as a supporting factor contributing to adolescents' social isolation, yet under certain conditions it also plays a role in assisting adolescents in overcoming social isolation.   Penggunaan media sosial berkontribusi terhadap kecenderungan isolasi sosial pada remaja. Penelitian ini bertujuan untuk mengkaji hubungan antara penggunaan media sosial dan isolasi sosial pada remaja di Provinsi Bengkulu, dengan mendeskripsikan kondisi dari fenomena isolasi sosial remaja dan fokus pada faktor-faktor yang mendorong individu menutup diri dari lingkungan sosial dengan menggunakan teori Ekologi Media dari Marshall Mcluhan. Penelitian ini menggunakan jenis kualitatif dengan pendekatan fenomenologi untuk mencari tahu secara mendalam terkait pengalaman subjektif remaja yang melakukan tindakan isolasi sosial. Data primer dikumpulkan melalui wawancara, observasi, dan dokumentasi sedangkan data sekunder melalui studi literatur. Analisis data dilakukan secara deskriptif analitik yang mencakup reduksi data, penyajian data, dan verifikasi. Hasil penelitian menemukan bahwa faktor eksternal yang berupa perilaku negatif yang diperoleh dari lingkungan sosial seperti (1). Dikhianati seseorang yang dipercaya (2). Pelecehan seksual (3). Komentar buruk, merupakan faktor utama yang menyebabkan seseorang melakukan tindakan isolasi sosial. Sedangkan faktor internal yang berupa perpektif individu, kondisi psikologis, dan kontribusi media sosial menjadi faktor pendukung tindakan isolasi sosial pada remaja. Remaja yang melakukan tindakan isolasi sosial akan rentan mengalami masalah mental seperti kesepian, stress dan depresi, sehingga pada kondisi seperti ini media sosial juga mampu berperan sebagai sarana rekreasi dan sumber dukungan psikologis yang membantu remaja melalui rasa kesepian. Maka dapat disimpulkan bahwasannya media sosial mampu menjadi faktor pendukung yang menyebabkan remaja melakukan tindakan isolasi sosial, namun dalam kondisi tertentu media sosial juga berperan sebagai sarana yang membantu remaja yang melakukan tindakan isolasi sosial.